Strategies for Strengthening Multicultural Education in Building Students Understanding of Religious Moderation - M. Ikhlashul Omar S; Fathurrahman Muhtar; Zainuddin Zainuddin (JURNAL PENDIDIKAN IPS, 2024)
Religious moderation is not created by itself, but there must be a joint effort and hard work to form and maintain religious consciousness, while multicultural education is an effort of learning carried out in institutions of formal and non-formal education in order to teach students the diversity of cultural, religious, and social attitudes and thinking of society. Therefore, the aim of this research is to find out the strategy for strengthening multicultural education by building student understanding of religious moderation in SMPN 14 Mataram. This research uses a qualitative-descriptive research approach. There are three ways of gathering data: observation, interview, and documentation. The results of the research proved that the school's strategy in the progress of strengthening multicultural education in building students' understanding of religious moderation in SMPN 14 Mataram has three important elements, namely, first, the moderation of the religious ritual activities; second, the moderation in the activities of the learning activity; and third, the moderation in the activities of the major religious days. What are the supportive factors in the progress of strengthening multicultural education in building students' understanding of religious moderation in SMPN 14 Mataram? The support of the citizens of SMPN 14 Mataram, teachers of the various SMPN, and the school provides the scope for students to develop their potential, while the inhibitory factors are the adaptation of students at the beginning of school entry and teachers lack of media on diversity in the school.